2010
DOI: 10.1592/phco.30.pt2.28s
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomics of Hepatic Encephalopathy

Abstract: Understanding and appreciating the science of pharmacoeconomics have become even more important for health care providers and insurers during the recent economic downturn. Evaluating the true costs of any disease is complex; both direct costs, such as costs of drug therapy and the provision of care, and indirect costs, such as lost earnings and reduced quality of life, must be taken into account. With chronic liver disease, the most recent data indicate that direct costs were more than $2 billion whereas indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Neomycin, rifaximin and metronidazol have been used (Shiano 2010). Rifaximin has good efficacy with less bacterial resistance and adverse effects than the other antibiotics, and thereby probably more cost-effective (Shiano 2010; Neff 2010). …”
Section: Discussion and Evaluationmentioning
confidence: 99%
“…Neomycin, rifaximin and metronidazol have been used (Shiano 2010). Rifaximin has good efficacy with less bacterial resistance and adverse effects than the other antibiotics, and thereby probably more cost-effective (Shiano 2010; Neff 2010). …”
Section: Discussion and Evaluationmentioning
confidence: 99%
“…Risk of hospitalization was the highest in the first year of life and decreased with increasing age . Cost per hospital stay for metabolic decompensation was estimated by Neff using patients with hepatic encephalopathy from the Healthcare Cost and Utilization Project. Estimate of percentage of patients with developmental delay was from the same study as the mortality estimates by de Baulny et al; other studies on this patient population report similar or worse developmental outcomes .…”
Section: Methodsmentioning
confidence: 99%
“…The average wholesale price for lactulose is about US$79 per month depending on the necessary dose 20. Previous studies have suggested a cost-effective benefit of rifaximin compared with disaccharides,21 but patient acceptability and adherence to treatment remains unclear. In this review, we will assess the safety, efficacy, and patient acceptability of maintenance therapy of HE.…”
Section: Introductionmentioning
confidence: 99%